2009
DOI: 10.1158/1078-0432.ccr-09-1467
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA Expression in Squamous Cell Carcinoma and Adenocarcinoma of the Esophagus: Associations with Survival

Abstract: Purpose: The dismal outcome of esophageal cancer patients highlights the need for novel prognostic biomarkers, such as microRNAs (miRNA). Although recent studies have established the role of miRNAs in esophageal carcinoma, a comprehensive multicenter study investigating different histologic types, including squamous cell carcinoma (SCC) and adenocarcinoma with or without Barrett's, is still lacking. Experimental Design: miRNA expression was measured in cancerous and adjacent noncancerous tissue pairs collected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
288
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(309 citation statements)
references
References 49 publications
15
288
3
3
Order By: Relevance
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51). Likewise, miR-15a was previously shown to be downregulated in metastasizing prostate carcinoma (18).…”
Section: Discussionmentioning
confidence: 80%
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51). Likewise, miR-15a was previously shown to be downregulated in metastasizing prostate carcinoma (18).…”
Section: Discussionmentioning
confidence: 80%
“…Compared with NEST, a significant down-regulation of miR-210 expression was noted in ESCC. On the other hand, the expression of miR-31, which has been reported to be not altered between ESCC and NEST (16,17), showed no significant difference (Fig. 1B).…”
Section: Mir-210 Expression Is Significantly Down-regulated In Escc mentioning
confidence: 77%
“…Until very recently, miR-375 has been found to be deregulated in some malignancies, including live tumor with β-catenin mutation, head and neck squamous cell carcinoma and pancreatic adenocarcinomas [26][27][28][29], whereas little is known about the molecular targets of miR-375 in these cancer. To our knowledge, JAK2 may be the first identified target gene that is involved in the regulation of carcinogenesis by miR-375.…”
Section: Discussionmentioning
confidence: 99%